The salt stress-induced LPA response in Chlamydomonas is produced via PLA(2) hydrolysis of DGK-generated phosphatidic acid - Arisz, Steven A. (The American Society for Biochemistry and Molecular Biology, 2011)
The unicellular green alga Chlamydomonas has frequently been used as a eukaryotic model system to study intracellular phospholipid signaling pathways in response to environmental stresses. Earlier, we found that hypersalinity induced a rapid increase in the putative lipid second messenger, phosphatidic acid (PA), which was suggested to be generated via activation of a phospholipase D (PLD) pathway and the combined action of a phospholipase C/diacylglycerol kinase (PLC/DGK) pathway. Lysophosphatidic acid (LPA) was also increased and was suggested to reflect a phospholipase A(2) (PLA(2)) activity based on pharmacological evidence. The question of PA's and LPA's origin is, however, more complicated, especially as both function as precursors in the biosynthesis of phospho- and galactolipids. To address this complexity, a combination of fatty acid-molecular species analysis and in vivo (32)P-radiolabeling was performed. Evidence is provided that LPA is formed from a distinct pool of PA characterized by a high α-linolenic acid (18:3n-3) content. This molecular species was highly enriched in the polyphosphoinositide fraction, which is the substrate for PLC to form diacylglycerol. Together with differential (32)P-radiolabeling studies and earlier PLD-transphosphatidylation and PLA(2)-inhibitor assays, the data were consistent with the hypothesis that the salt-induced LPA response is primarily generated through PLA(2)-mediated hydrolysis of DGK-generated PA and that PLD or de novo synthesis [via endoplasmic reticulum - or plastid-localized routes] is not a major contributor.